2019
DOI: 10.1080/10615806.2019.1617854
|View full text |Cite
|
Sign up to set email alerts
|

Sleep quality and treatment of social anxiety disorder

Abstract: Background and Objectives: Poor sleep is prevalent among individuals with social anxiety disorder (SAD) and may affect treatment outcome. We examined whether: (1) individuals with SAD differed from healthy controls (HCs) in sleep quality, (2) baseline sleep quality moderated the effects of treatment (Cognitive-behavioral group therapy [CBGT] vs. mindfulness-based stress reduction [MBSR] vs. waitlist [WL]) on social anxiety, (3) sleep quality changed over treatment, and (4) changes in sleep quality predicted an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 59 publications
0
24
0
3
Order By: Relevance
“…Good sleeping quality is important to the students in the study process, as it is essential for their mental wellbeing and is interrelated with anxiety [40,41]. In this study, we found that the sleeping habit was significantly associated with anxiety.…”
Section: Socio-demographic Characteristicsmentioning
confidence: 53%
“…Good sleeping quality is important to the students in the study process, as it is essential for their mental wellbeing and is interrelated with anxiety [40,41]. In this study, we found that the sleeping habit was significantly associated with anxiety.…”
Section: Socio-demographic Characteristicsmentioning
confidence: 53%
“…The sample size of each study was between 26 and 148. The majority of participants were females (61.3% females in 90.9% of the included studies) (35)(36)(37)(38)(39)(40)(42)(43)(44)(45). Individuals with anxiety disorders (38)(39)(40)42,43,45) accounted for 48.7%, while people with anxiety symptoms were 51.3%.…”
Section: Overview Of Participant Characteristicsmentioning
confidence: 99%
“…The courses of intervention of the five studies (35,41-44) were 8 weeks, whereas for other studies (37,39), it was 10-18 weeks per arm. Only one of the studies included anxiety, depression, and sleep quality outcomes (35), seven studies reported both anxiety and depression outcome measures (37,38,40,(42)(43)(44), while two reported anxiety and sleep quality outcomes (41,45). One of the studies could only extract the anxiety outcome (39).…”
Section: Overview Of Participant Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, another study found that individuals with co-occurring SAD and subjective sleep disturbances, compared to those without sleep disturbance, evidenced a more severe clinical presentation both at treatment onset and termination (Kushnir et al, 2014). Results from a recent study, however, found that baseline sleep quality did not moderate CBT treatment outcomes for SAD (Horenstein et al, 2019). Only one study to date has examined the withintreatment relation of sleep, in addition to baseline sleep, and exposure therapy.…”
Section: Introductionmentioning
confidence: 99%